Hubungan Pola Makan, Pola Konsumsi Kopi dan Status Merokok dengan Gejala Gastritis pada Remaja di Kecamatan Bekasi Utara tahun 2024 - Afifah Azmi; Rony Darmawansyah Alnur (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Symptoms of gastritis are found in gastritis sufferers, however, each person is certainly different, namely nausea, vomiting, discomfort in the stomach, pain in the pit of the stomach, diarrhea, decreased appetite resulting in weight loss, and bloating. Based on data from the disease pattern graph of outpatients at the Health Center in Bekasi City in 2020, the number of ulcer sufferers in Bekasi City was 3,464 sufferers. Gastritis is caused by poor diet, coffee consumption patterns and smoking status. The objective of this study is to analyze the correlation between eating habits, coffee consumption patterns, and smoking status with the occurrence of gastritis symptoms in adolescents in North Bekasi District.This study is a quantitative study with a Cross Sectional study design. The population in this study were adolescents living in the North Bekasi District area. Determination of the sample using Quota Sampling, data collection by observation and interviews. The data analysis technique used was Chi-Square. The results showed that out of 115 respondents, 61 respondents (53,0%) were at risk of gastritis symptoms and 54 respondents (47,0%) were not at risk of gastritis symptoms. There is a relationship between diet and gastritis symptoms (pvalue 0,005 < 0,05), there is a relationship between coffee consumption patterns and gastritis symptoms (pvalue 0,022 < 0,05), there is a relationship between smoking status and gastritis symptoms (pvalue 0,004 < 0,05).